Peran Guru Pendidikan Agama Kristen Dalam Mendisiplinkan Siswa Di SMK Negeri 1 Naibonat - Sem Saetban (Discreet: Journal Didache of Christian Education, 2021)
This study aimed to determine the role of Christian religious education teachers in disciplining students of the State 1 Naibonat Vocational High School. The research method used is qualitative research through observation, interviews, and documentation studies. The location of the study was carried out at the State Vocational High School 1 Naibonat; the subjects used in this study were four people consisting of 1 Christian religion teacher and three students. So the research results obtained are 1). Teachers as educators can form student discipline that has been carried out well; 2). Teachers, as mentors, always guide students when they violate school discipline; 3). Teachers as teachers; 4). Teachers as trainers; 5). Teachers as advisors have been carried out well, namely always advising students on the benefits of being obedient/obedient to school regulations; 6). The teacher acts as a mediator because he always informs students of media that are unknown to students: 7). Teachers as role models in improving the discipline of State Vocational High School students 1 Naibonat and 8). Teachers as motivators because Christian Religious Education teachers have many ways to motivate students to be disciplined through praise and gifts.